Phenotypic And Molecular Screening of Extended Spectrum β-Lactamase ESBLS in MDR- E. Coli Isolated from Urinary Tract Infection Cases (Journal of Pharmaceutical Negative Results, 2022)
E. coli is a significant infectious agent that causes nosocomial infections in hospitals all over the world. One of the factors that contributes to the development of drug resistance in E. coli is responsible for the production of ESBls enzymes. In this study, bla TEM was documented for the very first time among E. coli in Iraqi hospitals located in the province of Al-Anbar. 100 of the 141 E. coli clinical isolates tested for resistance to cephalosporins were found in urine samples. The VITEK-2 system was used to analyze antibiotic resistance. All of the isolates have been found to produce the cephalosporins gene, as shown by the positive results of the phenotypic detection of Extended-Spectrum βlactamases enzymes by the Modified Hodge test and the mCIM; 25/25 (100%) of the tests yielded a positive result with the mCIM, and 4.87 % with the modefied Hodge test. Traditional PCR was used to detect the bla TEM gene, and the results showed that 56% of the strains were positive for this gene. These findings demonstrated that TEM was present in MDR-E. coli, indicating that ESBLs were prevalent throughout the province of Anbar in Iraq.